Altered endoplasmic reticulum calcium loading in human PLN-R14del cardiomyopathy - Borbein, Willem; Dahmlos, Lukas; Saleem, Umber; Reinsch, Marina; Braren, Ingke; Schulze, Thomas; Klampe, Birgit; Cuello, Friederike; Stenzig, Justus; Eschenhagen, Thomas; Hansen, Arne (Frontiers in Cell and Developmental Biology, 2025)
The phospholamban (PLN) R14del genetic variant causes dilated cardiomyopathy. Previous studies suggest involvement of the ER stress response and impairment of ER-related signaling pathways such as autophagy. In this study, human-induced pluripotent stem cell (hiPSC)-derived cardiomyocytes (CMs) from an unrelated control subject, a PLN-R14del patient, and a corresponding isogenic control were transduced with adeno-associated virus serotype 6 (AAV6) encoding the endoplasmic reticulum calcium sensor CEPIAer. Indicator compounds for the modulation of ER calcium homeostasis showed similar characteristic effects on CEPIAer fluorescence intensity in engineered heart tissues (EHTs) from all three cell lines, validating CEPIAer fluorescence intensity as a surrogate for ER calcium loading. Cytoplasmic calcium loading induced by high extracellular calcium concentration revealed subtle alterations in PLN-R14del that were consistent with higher ER calcium loading. FACS analyses of dissociated cardiomyocytes confirmed higher ER calcium load. Taken together, this study provides evidence for altered ER calcium loading as a new disease mechanism in PLN-R14del cardiomyopathy.